Genesis of technologies and ways to improve design and construction of towed underwater systems for shallow-water areas - Blintsov, Volodymyr; Kucenko, Pavlo (Technology audit and production reserves, 2020)
The object of research is the design technology of towed underwater systems for shallow waters. The subject of research is ways to increase productivity and reduce the cost of designing and manufacturing towed underwater systems. During the research, the methodology of system approach, methods of structural analysis, mathematical modeling and 3D-design, additive technologies of manufacturing structures of towed underwater systems are applied. A systematic analysis of the laws of development of the technologies of designing towed underwater systems is performed. The perspective directions of their further development are formulated as a necessary condition for increasing the efficiency of design works on the basis of modern designing tools and ensuring competitiveness in the market of marine equipment. It is proposed to supplement the traditional stages of designing such systems with three new stages that embody the current trends in the creation of marine technology. The genesis of the technologies of designing towed underwater systems is developed as a scientific and methodological basis for their further development in the direction of increasing the efficiency of design works and reducing the cost of time and financial resources. It is theoretically substantiated the feasibility of developing technologies of design of towed underwater systems by introducing into the project practice three technologies: – technologies of information modeling of the basic steady and transient modes of towed underwater systems on the basis of system approach, supplemented by the criteria of cost estimation for their construction and operation; – technologies of the building information modeling as an information support for the design, construction and further operation of the generated towed underwater system; – additive technology of production of elements and units of the towed underwater system based on the results obtained from the previous technologies as an effective way to reduce the total costs of financial and time resources and reduce the cost of created towed underwater systems. The practical importance of the work is to confirm the efficiency and industrial perspective of the proposed technologies, which was obtained as a result of their partial introduction into the design and production practice when creating the towed glider project. Further research is planned to be conducted within the framework of the pilot project «Single Information Space for the Processes of Design, Construction and Operation of towed Underwater Systems», as well as by expanding the use of additive technologies during the construction of towed underwater systems.